Propuesta para la implementación de la norma ISO 45001 - 2018 en la empresa EDS la Granja TDD (2021)
This document studies the actual occupational health and safety management system from one company that it is called EDS LA GRANJA TDD. For the study, it is considered the technical standard NTC-ISO 45001 2018, which explains the requirements with guidance for use. This technical standard, allows identifying how the management system is going in the company. Likewise, the purpose of this document is doing a proposal of the technical standard for the actual management system, in order to improve it.